Penyuluhan Bahaya Narkoba Sebagai Strategi Preventif di Masyarakat Desa Tapos 1 Kecamatan Tenjolaya - Somantri, Fikri Indriana; Primarni, Amie; Rois, Ajun; Husenudin, Abdul; Rahmawati, Dian; Wijaya, Siska Putri; Nuraeni, Nuraeni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Drug abuse poses a serious threat to health, social well-being, and the future of the nation. This research employs a case study method by directly conducting socialization and education on the dangers of drugs to the community. The research aims to determine the effectiveness of outreach in increasing public knowledge and awareness of the dangers of drugs. The results of the study indicate that direct outreach is able to increase public understanding, foster an attitude of rejection towards drugs, and encourage active participation in prevention.